Analyse de l’association entre la densité/proximité de puits d’exploitation de pétrole et de gaz naturel et les concentrations de radon à l’intérieur des résidences du Nord-Est de la Colombie-Britannique - Bourdet, Emmanuel (2022)
Northeastern British Columbia (Canada) is a region of oil and gas exploitation. Oil and gas extraction activities can emit contaminants, including radon, but studies on indoor air contaminants in regions of oil and gas exploitation are scarce. This study aimed to evaluate the association between the density/proximity of oil and gas wells and indoor air radon concentrations in Northeastern British Columbia. Data from the British Columbia Radon Data Repository (BCRDR) and the Exposures in the Peace River Valley study (EXPERIVA) were used, with 497 radon measurements taken from dwellings between 1992 and 2019. Within different buffer zones around each dwelling (2.5, 5 and 10 km), well density was calculated and an exposure metric, Inverse Distance Weighting (IDW), of both well density and proximity was derived. Linear regression models were used to evaluate the associations between well density and IDW and indoor air radon concentrations while adjusting for the floor where measurement was taken. A higher radon concentration was measured in basements than upper floors. Statistically significant and negative associations (p<0.05) were observed between well density/proximity and radon concentrations. For example, an increase of one well within 10 km was associated with a modest decrease of 0.1% (95% CI: 0.05; 0.20) in radon concentrations. We observed no positive association between well density/proximity measurements and radon concentrations. The negative associations were primarily influenced by radon measurements made in 1992, when oil and gas development used very little hydraulic fracturing. Additional studies with more measurements, information on dwelling type, and phase of oil and gas operations could allow a more precise and powerful analysis. L’exploitation gazière et pétrolière, parfois associée à de la fracturation hydraulique, peut entraîner l’émission de contaminants comme le radon dans les régions présentant des puits d’exploitation. L’objectif de cette étude était d’évaluer l’association entre la ...